Study of Colour Blindness in Tibetan Population - Navjot Kaur; Avinash Kumar; Gurinder Kaur; Jasjeet Kaur Dhillon; K.D. Singh (Delhi Journal of Ophthalmology)
Of the 1210 male and 800 female Tibetan population in Northern India between the age group of 11-60 years, 51 males and no female were found to be having colour blindness, showing an incidence of 4.21 % and 0% respectively. The study was done with the help of Ishihara charts and Pickford Nicolson’s anomaloscope. The type of colour blindness in males in its descending order of occurrence was simple deuteranomaly 27.45% protanopia 17.64%, deuteranopia 17.64%, extreme deuteranomaly 15.68%, protanomaly 13.72%, extreme protanomaly 5.88% and tritanopia 1.96%. None of the female was colour blind. The incidence and type of colourblidness found in males is within the range of other Indian samples. Nevertheless the incidence is much lower than the values reported in European populations but is much higher than the values reported in African populations.